Emphasizing Planning for Essay Writing With a Computer-Based Graphic Organizer. (January 2016) - Evmenova, Anya S.; Regan, Kelley; Boykin, Andrea; Good, Kevin; Hughes, Melissa; MacVittie, Nichole; Sacco, Donna; Ahn, Soo Y.; Chirinos, David
The authors conducted a multiple-baseline study to investigate the effects of a computer-based graphic organizer (CBGO) with embedded self-regulated learning strategies on the quantity and quality of persuasive essay writing by students with high-incidence disabilities. Ten seventh- and eighth-grade students with learning disabilities, emotional and behavioral disorders, attention deficit hyperactivity disorder, and autism spectrum disorder participated in the study. The authors collected data on the number of words, sentences, transition words, essay parts, and holistic writing quality score across (a) baseline (writing on the computer without the CBGO), (b) CBGO-use phase (writing on the computer with the CBGO), and (c) maintenance (writing on the computer without the CBGO). In a visual analysis, all participants improved the quality of their writing, and the majority of students also increased the quantity of their writing. Student interview data are presented to discuss the social validity of this innovative technology-based intervention.